DEVELOPMENT OF THE COMPOSITION OF EMULSION COSMETIC CREAM WITH MARINE COLLAGEN EXTRACT - YEFIMOVA, VERONIKA; PILIPENKO, TETIANA; SIRENKA, OLEKSANDRA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The work is devoted to the development of an emulsion cosmetic product using marine collagen extract. Fish and fish products are an important component in the diet, and for the population of a number of countries - the main food. Marine collagen extract is a functional biopolymer collagen - a protein that, due to its unique physical and chemical properties, has found application in the production of cosmetics. The marine environment represents an underexploited resource for the discovery of novel products, despite its high level of biological and chemical diversity. With increasing awareness of the harmful effects of chronic ultraviolet exposure, and a universal desire to improve cosmetic appearance, the market for new cosmetic ingredients is growing, and current trends have generated a greater demand for products sourced from the environment. A growing number of novel molecules from marine flora and fauna exhibit potent and effective dermatological activities. To date, not a single cosmetic company in Ukraine produces emulsion cosmetic products with marine collagen extract. The skin is constantly in contact with the environment and is subjected to various types of interactions: thermal, mechanical, physical, chemical, etc. Some of these influences adversely affect it. As a result, damage to the skin often occurs, accompanied by a violation of the structure and integrity of the skin. Collagen takes part in the rejuvenation of skin cells, and is also responsible for water balance and absorption of nutrients. This paper presents the development of the formulation of an emulsion cosmetic skin care product, as well as the study of the physicochemical parameters of a new product. The calculation of the hydrophilic-lipophilic balance made it possible to optimally select the ratio of the oil phase, emulsifier and co-emulsifier. The emulsion cosmetic product was prepared using the hot-hot process method. Thermal stability, colloidal stability and pH were studied as physical and chemical indicators. The research results made it possible to develop a formulation for a cosmetic emulsion cream using marine collagen extract.